Modern Tendencies of Development of Native Language Education of Ukrainians Abroad - Romaniuk, Svitlana (Pedagogical Discourse, 2014)
The factors, which influenced over formation of the language policy of Ukrainian western Diaspora and, accordingly, the development of native language education of Ukrainians abroad have been analyzed in the article. It is found out that in the far abroad countries it is provided by native schools, schools and courses of Ukrainian studies, state bilingual schools or bilingual classes, faculties in the Universities, special educational courses. Scientific-didactic accompanying of teaching the language as a mother tongue and the second language is guaranteed by the methodological center of Ukrainian language, which is founded in University of Alberta (Canada). The role of language as the basic means of forming national consciousness and preserving ethnocultural identity of the Diaspora Ukrainians has been determined.